Does elite success trigger mass participation in table tennis? An analysis of trickle-down effects in Germany, France and Austria - Haut, J.; Gaum, C. (Journal of Sports Sciences, 2018)
There is a widespread belief that success at the elite level leads to increasing mass participation in sports. However, this assumption is merely supported by empirical evidence and is analyzed here for the case of table tennis. Therefore long-term data (1964-2014) on participation in Germany, France and Austria is statistically tested for effects of success by the countries` athletes at international competitions. Results indicate that no general trickle-down effect can be confirmed for table tennis in the countries observed. Rather, findings are ambivalent, as a strong positive effect was found for the Austrian case, but a paradox relation for the German case, where elite success has been accompanied by decreasing participation in the last decades. Accordingly, as an "automatic" trickle-down effect is unlikely, more specific analyses and strategies seem necessary to use elite success as a lever for the promotion of the sport.